Perbaikan Tingkat Kebisingan pada Ruang Produksi Yessy’s Collection dengan Pendekatan Ergonomi - Afgan Suffan Aviv; Bambang Suhardi; Pringgo Widyo Laksono (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2017)
Implementation of ergonomics is generally a design or redesign. One of them may include the design of the physical work environment. Ergonomic work environment conditions are provide comfort and security for workers. Physical environmental factors that can affect the comfort and safety of noise level. A good physical work environment will increase work capability or labor productivity. In a work environment, workload assessment can also be carried out to measure worker conformity and comfort. Workload assessment is carried out simultaneously with measurement of noise level . Whose problematic noise, the industry is located in Tawangsari RT 03 RW 34 Mojosongo, Jebres, Surakarta named Yessy's Collection. Measurement of noise level to improve worker comfort, so that productivity increases. The methode used is measurement using 4 in 1 Environment on sound level meter function illustrated with Software Surfer 11. The noise level measurement results are below the specified threshold value except at 1 coordinate in swabing station (stasiun penyesekan),that is at above threshold value. To proposed improvements as noise control is engineering control, administrative control and use of PPE